Lipid-modifying pharmacotherapy in diabetes mellitus: A protocol for a systematic review and network meta-analysis of randomised trials - Xudong Zhao; Cheng Tang; Tianqi Yuan; Jiafan Chen; Cuijuan Shi; Xiaoyu Liu; Ruigeng Yang; Yushang Zhi; Wenrui Huang; Chunyan Zhu; Yu Chen; Shidong Wang (PLoS ONE, 2026)
Introduction The global prevalence of diabetes mellitus (DM) has risen markedly, with patients facing a substantially higher risk of atherosclerotic cardiovascular disease (ASCVD) and related mortality. Although lipid-modifying agents, including statins, fibrates, cholesterol absorption inhibitors, proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i), bromodomain and extra-terminal motif inhibitors (BETi), and adenosine triphosphate-citrate lyase inhibitors (ACLi) continue to emerge, their comparative efficacy and safety in patients with DM remain uncertain. This study aims to address this gap through a comprehensive network meta-analysis (NMA) of randomized controlled trials (RCTs) evaluating cardiovascular outcomes, lipid-modifying efficacy, and safety among these therapies. Methods and analysis A systematic search will be performed in PubMed, Web of Science, Scopus, the Cochrane Central Register of Controlled Trials (CENTRAL), Embase (via Ovid), International Clinical Trials Registry Platform (ICTRP) and ClinicalTrials.gov from inception, without language or regional restrictions. Eligible studies will include parallel-design RCTs comparing monotherapy or combination therapy. The primary outcome will be cardiovascular events (composite and individual), and secondary outcomes will include cardiac biomarkers, ASCVD risk scores, lipid parameters (TC, LDL-C, HDL-C, TG) and safety outcomes. Two reviewers will independently conduct study selection, data extraction, and quality assessment using the Cochrane Risk of Bias 2 (RoB 2.0) tool, with evidence certainty evaluated via the Confidence in Network Meta-Analysis (CINeMA) framework. Data will be standardized where appropriate, and analyses, including assessment of publication bias, will be conducted using Stata 18 and R. The protocol is registered with PROSPERO, and findings will be disseminated through peer-reviewed publication. Registration: PROSPERO CRD420251163974.